Nicotinamide phosphoribosyltransferase aggravates inﬂammation and promotes atherosclerosis in ApoE knockout mice - Kong Yuan-yuan; Li Guo-qiang; Zhang Wen-jie; Hua Xia; Zhou Can-can; Xu Tian-ying; Li Zhi-yong; Wang Pei; Miao Chao-yu (Acta Pharmacologica Sinica, 2019)
Nicotinamide phosphoribosyltransferase (Nampt) is the rate-limiting enzyme of nicotinamide adenine dinucleotide (NAD) salvage biosynthesis in mammals, and is involved in fundamental physiological processes and pathophysiology of many diseases. Thus far, however, the role of Nampt in atherosclerosis development is still in debate. In this study, we crossed global Nampt transgenic mice (Nampt-Tg) with a well-established atherosclerosis animal model (ApoE knockout mice, ApoE−/−) to generate ApoE−/−;Nampt-Tg mice and investigated the effects of Nampt overexpression on atherosclerosis development in ApoE−/− mice. Both ApoE−/− and ApoE−/−;Nampt-Tg mice were fed with a pro-atherosclerotic high-fat diet (HFD) for 16 weeks. Their serum lipid contents and atherosclerotic lesion were assessed. The results showed that there was no significant difference in body weight or serum levels of glucose, total cholesterol, triglycerides, high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol between the two strains of mice, but ApoE−/−;Nampt-Tg mice had a significantly higher level of serum non-esterified fatty acid. Compared with ApoE−/− mice, ApoE−/−;Nampt-Tg mice displayed significantly increased atherosclerotic lesion area and thickness, lower collagen content, decreased collagen I/III ratio (collagen immaturation), increased number of apoptotic cells, and enhanced activities of caspase-3, caspase-8, and caspase-9. Moreover, macrophage infiltration (F4/80 staining), tumor necrosis factor signaling, and chemokines expression (ICAM-1 and CXCR-4) were all activated in aortic atherosclerotic plaque of ApoE−/−;Nampt-Tg mice compared with ApoE−/− mice. Our results provide in vivo evidence that Nampt transgene aggravates atherosclerotic inflammation and promotes atherosclerosis development in ApoE−/− mice.